Discrimination between healthy and tumor tissues on formalin-fixed paraffin-embedded breast cancer samples using IR imaging. Issue 1 (2010) - Bénard Bénard, Audrey Audrey; Desmedt Desmedt, Christine Christine; Durbecq Durbecq, Virginie Virginie; Rouas Rouas, Ghizlane Ghizlane; Larsimont Larsimont, Denis Denis; Sotiriou Sotiriou, Christos Christos; Goormaghtigh Goormaghtigh, Erik Erik
Abstract : This work presents a pilot study to illustrate the potential of Fourier transform infrared (FT-IR) imaging in breast cancer research. Using this technique, we have acquired infrared (IR) microspectroscopic images from healthy and cancerous breast tissue section from one patient. First of all, a Student t -test was applied, showing DNA/RNA spectral region (1400–1000 cm −1 ) as the most discriminant for the differentiation between healthy and tumor samples. Afterwards, a supervised pattern recognition method, Partial Least Squares (PLS) was used to develop an automated classifier to discriminate the two classes of data. Infrared spectra of independent IR measurements were used to test the classifier. The class identity was correlated with information obtained by histopathologic gold standard. The results showed that more than 95% of the training and validation spectra were correctly identified. We demonstrate that combination between IR microspectroscopic imaging and multivariate data analysis can be used as a complement to present diagnostic tools for breast cancer.